(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The successions exposed in the Pin and Spiti valleys, a classical area for the Tethyan Triassic, provides an extraordinarily complete sedimentary and paleontologic record and is thus well-suited to check the validity of global eustatic charts and applicability of sequence stratigraphic concepts. New detailed stratigraphic data allowed us to present a revised lithostratigraphic scheme - largely based on previous works by Hayden (1904) and Srikantia (1981) - which can be directly compared with successions exposed all along the Tethys Himalaya from Zanskar to Tibet. The Permian/Triassic boundary represents a major break in sedimentation, with time gaps of up to several Ma testified in the upper Pin valley. In the Induan to Anisian, the Tamba Kurkur Fm. mainly documents global eustatic changes, with transgressive stages characterized by sedimentation of condensed nodular Lmestones on the outemost shelf/uppermost slope (e.g., Griesbachian/Early Dienerian, Spathian) and regressive stages marked by mudrock deposition on the continental shelf (e.g., Late Dienerian/Smithian). A glauconitic condensed horizon occurs at the Anisian/Ladinian boundary, and the top of the formation reaches the Early Ladinian in more complete proximal sections. Greater clay supply characterizes the late Early Ladinian, but accumulation rates remain low in the lower part of the Hanse Group(Kaga and Chomule Fms.), to increase sharply in the late Early to early Late Carnian ("Grey beds"), reaching 100 m/Ma in the latest Carnian (Nimaloksa Fm.). At least nine, third- to fourth-order transgressive,/regressive sequences can be recognized in the Nimaloksa Fm. and Alaror Group, where facies distribution pattems indicate that the Spiti continental margin deepened towards the north. The Nimaloksa Fm. documents progradation of a carbonate ramp in the latest Carnian(Lower Member), followed in the Early Norian by subtidal mixed carbonate/terrigenous sedimentation (Middle Member) and by platform carbonate deposits (Upper Member). Next, the major disconformity at the base of the Alaror Group testifies to an extensional tectonic event, followed by rapid increase in quanzo-feldspathic detritus in the late Early Norian. Siliciclastic supply is reduced only during flooding stages, marked by oolitic ironstone or phosphatic condensed horizons ("Juvavites beds", "Monotis shale’); cleaner waters foster local development of knoll reefs round the Early/Middle Norian boundary ("Coral limestone’). Accumulation rates gradually begin to decrease before the close of the Triassic, when the "Quartzite series" records a sharp regressive event, followed by renewed transgression at the base of the Kioto Group.